How is Reflective Practice in Learning? A Science Teachers Perspective - Babutta, Selvies Lea; Riandi, Riandi; Kaniawati, Ida; Hendayana, Sumar (KnE Social Sciences, 2024)
Reflective is a thinking process that can be carried out by teachers, leading to improvements in effective classroom management and quality and improving student performance, so that reflective practices are indispensable in teaching and learning practices. This study aims to describe the reflective practice of science teachers in junior high schools. Primary data were collected based on the teacher’s experience in teaching science learning, highlighting three aspects including reflective action, the form of reflective action, and follow-up to reflective activities. This qualitative study was conducted through the distribution of online questionnaires. The results indicate that reflective action in learning by science teachers is always carried out, but the form of reflective action has not yet involved many peers, principals, and supervisors. Most often done by teachers themselves, to accept other people’s thoughts, learn, or share good practices have not fully occurred. The follow-up of reflective activities has not been followed by changes to the design of further learning in the lesson plan, but teachers are more focused on changing the teaching process that they do in class independently. Keywords: reflective practice, science teachers, perspective